2014
DOI: 10.15837/ijccc.2012.5.1349
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Main Functionalities Required by Semantic Search in Decision-Support Systems

Abstract: Abstract:This paper exploits different semantic web technologies and builds a prototype of semantic web mashup functionality based on an architecture proposed by us. The main scope is to improve decision-making processes. In this paper, we are focusing on querying different ontologies in order to improve decision-making semantic search. As a conclusion, we demonstrate that in order to improve decision-making semantic search there is a need of special constructions that a query language must support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Input data in the decision-making model is changing (from personal to mass collab-15 oration and integration of external data), although the semantic web is not a decisionmodelling technology to improve decision per se, but perhaps more a possibility of integrating data (Necula, 2011). Therefore, improving the search, enhancing knowledge sharing and integrating the available, though heterogeneous, databases and semantic interoperability, will reveal implicit information that usually would remain undiscov-20 ered, thereby resulting in suboptimal decisions (Necula, 2012).…”
Section: Aq18mentioning
confidence: 99%
“…Input data in the decision-making model is changing (from personal to mass collab-15 oration and integration of external data), although the semantic web is not a decisionmodelling technology to improve decision per se, but perhaps more a possibility of integrating data (Necula, 2011). Therefore, improving the search, enhancing knowledge sharing and integrating the available, though heterogeneous, databases and semantic interoperability, will reveal implicit information that usually would remain undiscov-20 ered, thereby resulting in suboptimal decisions (Necula, 2012).…”
Section: Aq18mentioning
confidence: 99%
“…The pressure exerted by automation and digitalisation is not naturally absorbed at the educational sector or organisation level, which Reference [22] describes as rather past-oriented, conveying and using obsolete information that is inert compared to innovation. Moreover, in References [23][24][25] is shown that individuals that cannot develop high-level skills, cannot cope with the pressure of using Information and Communication Technologies (ICT) in the workplace and are not sufficiently autonomous feel threatened, insecure and confused, which results in their failure to carry out their job duties and even quitting their jobs.…”
Section: The Need For Lifelong Learning An Approach From the Point Omentioning
confidence: 99%
“…A significant part of research was focused on cloud computing security [120] and on quality of services. This quality has to include both customer satisfaction [121] and meeting the requirement of environmental protection. The design of a green cloud has two types of challenges: technical and non-technical.…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%